2008
DOI: 10.1002/we.262
|View full text |Cite
|
Sign up to set email alerts
|

HAWT near‐wake aerodynamics, Part I: axial flow conditions

Abstract: An improved physical understanding of the rotor aerodynamics of a horizontal axis wind turbine (HAWT) is required to reduce the uncertainties associated with today's design codes. Wind tunnel experiments contribute to increased knowledge and enable validation and construction of models. The present study focuses on the near-wake of a model HAWT in both axial and yawed flow conditions. At three downstream planes parallel to the rotor plane, single-sensor hot-film traverses are made. The phase-locked unsteady th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 20 publications
1
21
0
1
Order By: Relevance
“…A NACA0012 profile is used on the lifting part of the blade from r/R=0.3 up to the tip, and the blade has constant chord length of 0.08m with linear twist distribution. Detailed information regarding the wind turbine and the research program of TUDelft can be found in the works of Sant [15] and Haans et al [16]. The blade can be pitched at different angles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A NACA0012 profile is used on the lifting part of the blade from r/R=0.3 up to the tip, and the blade has constant chord length of 0.08m with linear twist distribution. Detailed information regarding the wind turbine and the research program of TUDelft can be found in the works of Sant [15] and Haans et al [16]. The blade can be pitched at different angles.…”
Section: Resultsmentioning
confidence: 99%
“…Several adaptations are necessary to ensure numerical convergence and are presented. Comparisons between numerical results and experimental measurements are presented for the TUDelft experimental rotors [16].…”
Section: Introductionmentioning
confidence: 99%
“…The validation of the free-vortex wake method for a wind turbine in axial flow was performed against the wake geometry measurements obtained by Haans et al 6 . In addition, aerodynamic analysis of NREL Phase VI rotor 7 was…”
Section: Resultsmentioning
confidence: 99%
“…(a) Schematic of the experimental test setup (b) Tip vortex for Λ=0°, λ=8, and θtip=2° Present Experiment [6] Reference [3] a) Tip vortex geometry for θtip= 0° (b) Tip vortex geometry for θtip= 2° (c) Tip vortex geometry for θtip= 4° Fig. 2.…”
Section: Wake Geometry Validation (Haans Et Al Experiment)mentioning
confidence: 99%
See 1 more Smart Citation